Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1128/aem.72.4.2514-2519.2006
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the P450 Monooxygenase NysL, Responsible for C-10 Hydroxylation during Biosynthesis of the Polyene Macrolide Antibiotic Nystatin in Streptomyces noursei

Abstract: The nysL gene, encoding a putative P450 monooxygenase, was identified in the nystatin biosynthetic gene cluster of Streptomyces noursei. Although it has been proposed that NysL is responsible for hydroxylation of the nystatin precursor, experimental evidence for this activity was lacking. The nysL gene was inactivated in S. noursei by gene replacement, and the resulting mutant was shown to produce 10-deoxynystatin. Purification and an in vitro activity assay for 10-deoxynystatin demonstrated its antifungal act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 29 publications
(45 reference statements)
1
36
0
1
Order By: Relevance
“…The MIC value of BSG022 was similar to that of S44HP ( Table 3), indicating that the C-10 hydroxyl removal had no significant effect on the antifungal activity, which was in agreement with the previous report on 10-deoxynystatin (23). The HC 50 value of BSG022 was more than 2-fold reduced compared to that of S44HP, suggesting increased toxicity to erythrocytes.…”
Section: Vol 77 2011 New Polyene Macrolides With Engineered Polyol supporting
confidence: 80%
See 1 more Smart Citation
“…The MIC value of BSG022 was similar to that of S44HP ( Table 3), indicating that the C-10 hydroxyl removal had no significant effect on the antifungal activity, which was in agreement with the previous report on 10-deoxynystatin (23). The HC 50 value of BSG022 was more than 2-fold reduced compared to that of S44HP, suggesting increased toxicity to erythrocytes.…”
Section: Vol 77 2011 New Polyene Macrolides With Engineered Polyol supporting
confidence: 80%
“…In order to determine whether the effect on biological activity observed for the BSG003 and BSG018 molecules was due to the changes at C-9 or C-10, we decided to remove a single C-10 hydroxyl from the S44HP and BSG005 analogues. In a previous report we demonstrated that inactivation of the P450 mono-oxygenase gene nysL in S. noursei resulted in a mutant strain, designated NLD101, which produced 10-deoxynystatin with antifungal activity similar to that of the parental antibiotic nystatin (23). However, the hemolytic activity of 10-deoxynystatin has not been tested.…”
Section: Vol 77 2011 New Polyene Macrolides With Engineered Polyol mentioning
confidence: 99%
“…SelL, a cytochrome p450 with homology to the p450 NysL that installs nystatin's C10 hydroxyl, is the most probable oxidase for C4 (38). We also identified SelP, a 2-oxoglutarate-dependent oxygenase with homology to phytanoylCoA dioxygenases.…”
Section: Chemistrymentioning
confidence: 85%
“…This construct was introduced into S. nodosus, and polyenes were extracted and analyzed by HPLC. The main products were amphotericins A (7) and B (3). No extra polyene species were detected as convincing peaks in the chromatograms, but ESMS analysis of the crude polyenes revealed additional trace ions with molecular masses appropriate for mannosyl-amphotericin A (10) …”
mentioning
confidence: 97%
“…In some cases, another P450 subsequently introduces a hydroxyl group or epoxide. 3,4) Chemical modification studies have shown that adding sugar residues to polyenes can improve their pharmacological properties. [5][6][7] Enzymatic methods of extending natural product glycosylation have been developed in recent years.…”
mentioning
confidence: 99%